Evaluation of endoscopic and microscopic approaches in pediatric patients who undergo type 1 tympanoplasty (Annals of Medical Research, 2025)
Aim: In the present study, we aimed to investigate endoscopic and microscopic type 1 tympanoplasty outcomes in pediatric patients.Materials and Methods: In this retrospective analysis, we assessed a total of 134 patients. The study focused on the outcomes of 138 ears from these 134 pediatric patients who received type 1 tympanoplasty. Four patients had the procedure performed on both ears. The ages of the patients varied from 7 to 16 years. They were categorized into two groups based on the surgical technique employed. Group 1 consisted of patients who had type 1 tympanoplasty via an endoscopic method (n=58), while Group 2 included those who underwent the microscopic approach to type 1 tympanoplasty (n=80). The tympanic membrane was repaired using cartilage graft obtained from tragus cartilage in all patients. The outcomes (regaining hearing, graft success, duration of operation, etc.) of the patients in both groups were analyzed.Results: The postoperative air-bone gap (ABG) in both groups was statistically lower than preoperative ABG. The pre-operative ABG of group 1 and group 2 were comparable with and no significant difference among the groups. Likewise, postoperative ABG of groups 1 and 2 showed no significant difference among the groups. The duration of operation of group 1 was statistically shorter than the durartion of operation ofgroup 2. The graft success rates of group 1 and group 2 were 94.55% and 94.74%, respectively; p = 0.309).Conclusion: As in adults, type 1 tympanoplasty can be safely performed in children with an endoscopic approach. The most important advantage of this procedure is better visualization of the entire tympanic membrane in patients who have  narrow external auditory canals. Although the regain rate of hearing of the groupswere , endoscoğic approach has shorter duration of operation and  the duration of postoperative care were shorter than the  microscopic approach.
Keywords: Endoscopic ear surgery; Microscopic ear surgery; Chronic otitis media; Pediatric tympanoplasty; Tympanoplasty